The Effect of the Tourism Sector on Labor Absorption in Sumbawa Regency - Muhammad Hidayat Juliansyah; Satarudin, Satarudin; Gusti Ayu Arini (Tinta Emas Publisher, 2024)
Tourism plays an important role in the Indonesian economy both as a source of foreign exchange earnings and as a creator of employment and business opportunities. This study aims to determine how much influence the number of hotels, the number of restaurants, the number of tourist objects, and the number of tourists have on labor absorption in Sumbawa Regency. The method used in this research is quantitative research method. The data used is secondary data taken from the Nusa Tenggara Barat Provincial Statistics Agency, the Sumbawa Regency Statistics Agency, and the Sumbawa Regency Youth, Culture and Tourism Office. The data analysis method uses multiple linear regression through the eviews10 program. The data in this study are time series data (data from 2013-2023). The results of this study indicate that the variables of Number of Hotels, Number of Restaurants, Number of Tourist Objects, and Number of Tourists have a positive and significant effect on Labor Absorption in the tourism industry in Sumbawa Regency. From the test value of the coefficient of determination (R2) that the variable effect of the number of hotels, the number of restaurants, the number of tourist objects and the number of tourists on the labor absorption variable produces a value of 0.94051 or 94%. While the remaining 6% is explained by other variables that do not exist or outside the study.